The healthy PC preventive care, home remedies, and green computing - Davis, Guy Hart (New York McGraw-Hill, 2012)
"The latest techniques for keeping your PC running at peak performance--without spending a lot of money!Written by the co-host of the longest-running, nationally syndicated radio talk show on computers, "Computer America", The Healthy PC, Second Edition shows you how to maintain your PC's performance and prevent problems before they happen. Using easy-to-follow steps and clear instructions, the book teaches you how to keep your computer in top condition, diagnose and fix common problems, and improve overall performance. No prior experience or knowledge is needed! Get tips on saving money with free, quality software and free tech support websites. The author developed his approach to teaching computer maintenance skills out of more than 20 years of PC repair experience and talking with thousands of customers about their questions and concerns. Learn from the expert!The Healthy PC, Second Edition Provides easy-to-follow, step-by-step instructions with illustrations Shows you how to be proactive with preventive maintenance and how to detect problems before they happen Features clear and concise language that makes computer terms and concepts easy to understand Recommends the best free software and tech support websites that can save you thousands of dollars Practical, in-depth coverage: Upgrading Your Operating System; 32-bit vs. 64-bit; The Internet; How to Surf Safely; E-mail, Spam, and Hoaxes; Optimizing Your Internet Connection; Preventive Maintenance; System Optimization Tips & Tricks; Other Ways to Increase System Performance; Backing Up Your Computer; Computer Security; Anti-virus, Anti-spyware, and Firewalls."
"Save yourself time, money, and frustration by becoming your own computer guru. The Healthy PC: Preventive Care, Home Remedies, and Green Computing, Second Edition shows you how to find out what's wrong with your PC and solve the problems yourself. You'll get expert tips for making your PC start up faster, keeping its hard drive in good shape, and updating Windows with the latest security fixes. This hands-on guide also explains how to protect your PC for free using Microsoft Security Essentials, use the Internet safely, and configure parental controls to protect your children both online and offline."
Part I. Preventive Maintenance -- Chapter 1 System Optimization Tips & Tricks -- Chapter 2 Other Ways to Increase System Performance -- Chapter 3 Backing Up Your Computer -- Part II Computer Security -- Chapter 4 Anti-virus, Anti-spyware, and Firewalls -- Chapter 5 E-mail, Spam, and Hoaxes -- Chapter 6 Passwords -- Part III The Internet -- Chapter 7 The Dangers of WiFi -- Chapter 8 How to Surf Safely -- Chapter 9 Optimizing Your Internet Connection -- Part IV Operating Systems -- Chapter 10 Upgrading Your Operating System -- Chapter 11 32-bit vs. 64-bit: What Does It Mean and Why Should You Care? -- Appendix A What to Do When Things Go Wrong -- Appendix B Free Technical Support -- Appendix C Computer User Groups -- Appendix D 50 Safe and Free Software Utilities Recommended by Steve Bass -- Appendix E Safe and Free Software Recommended by Mr. Modem.
Revied edition of: The healthy PC / Carey Holzman. 2003.
Includes index.
Keywords: Microcomputers -- Maintenance and repair; Computers -- General